Oxidative stress markers are elevated in exhaled breath condensate of workers exposed to nanoparticles during iron oxide pigment production - Pelclova, Daniela; Zdimal, Vladimir; Kacer, Petr; Fenclova, Zdenka; Vlckova, Stepanka; Syslova, Kamila; Navratil, Tomas; Schwarz, Jaroslav; Zikova, Nadezda; Barosova, Hana; Turci, Francesco; Komarc, Martin; et al. (Journal of breath research, 2016)
Markers of oxidative stress and inflammation were analysed in the exhaled breath condensate (EBC) and urine samples of 14 workers (mean age 43 ± 7 years) exposed to iron oxide aerosol for an average of 10 ± 4 years and 14 controls (mean age 39 ± 4 years) by liquid chromatography-electrospray ionization-mass spectrometry/mass spectrometry (LC-ESI-MS/MS) after solid-phase extraction. Aerosol exposure in the workplace was measured by particle size spectrometers, a scanning mobility particle sizer (SMPS) and an aerodynamic particle sizer (APS), and by aerosol concentration monitors, P-TRAK and DustTRAK DRX. Total aerosol concentrations in workplace locations varied greatly in both time and space. The median mass concentration was 0.083 mg m(-3) (IQR 0.063-0.133 mg m(-3)) and the median particle concentration was 66 800 particles cm(-3) (IQR 16,900-86,900 particles cm(-3)). In addition, more than 80% of particles were smaller than 100 nm in diameter. Markers of oxidative stress, malondialdehyde (MDA), 4-hydroxy-trans-hexenale (HHE), 4-hydroxy-trans-nonenale (HNE), 8-isoProstaglandin F2α (8-isoprostane) and aldehydes C6-C12, in addition to markers of nucleic acid oxidation, including 8-hydroxy-2-deoxyguanosine (8-OHdG), 8-hydroxyguanosine (8-OHG), 5-hydroxymethyl uracil (5-OHMeU), and of proteins, such as o-tyrosine (o-Tyr), 3-chlorotyrosine (3-ClTyr), and 3-nitrotyrosine (3-NOTyr) were analysed in EBC and urine by LC-ESI-MS/MS. Almost all markers of lipid, nucleic acid and protein oxidation were elevated in the EBC of workers comparing with control subjects. Elevated markers were MDA, HNE, HHE, C6-C10, 8-isoprostane, 8-OHdG, 8-OHG, 5-OHMeU, 3-ClTyr, 3-NOTyr, o-Tyr (all p < 0.001), and C11 (p < 0.05). Only aldehyde C12 and the pH of samples did not differ between groups. Markers in urine were not elevated. These findings suggest the adverse effects of nano iron oxide aerosol exposure and support the utility of oxidative stress biomarkers in EBC. The analysis of urine oxidative stress biomarkers does not support the presence of systemic oxidative stress in iron oxide pigment production workers.
Keywords: Malondialdehyde; Aldehydes; guanosin; malondialdehyd; Nanoparticles; dinoprost; Middle Aged; mužské pohlaví; Dinoprost; Oxidative Stress; Adult; Ferric Compounds; tyrosin; Guanosine; Tyrosine; železité sloučeniny; Humans; dechové testy; Breath Tests; Tandem Mass Spectrometry; biologické markery; nanočástice; lidé středního věku; tandemová hmotnostní spektrometrie; dospělí; oxidační stres; Biomarkers; lidé; Male; aldehydy